2013
DOI: 10.1007/s40273-013-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Treatment and Outcomes Patterns Simulation: A New Framework for Evaluating the Potential Health and Economic Impact of Smoking Cessation Interventions

Abstract: By allowing for multiple quit attempts over the course of individuals' lives, the simulation can provide more reliable estimates on the health and economic impact of interventions designed to increase abstinence from smoking. Furthermore, the individual nature of the simulation allows for evaluation of outcomes in populations with different baseline profiles. DES provides a framework for comprehensive and appropriate predictions when applied to smoking cessation over smoker lifetimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…The population prevalence of each comorbidity and relative risk for a smoker versus a former smoker were taken from various sourcesthe sources are shown in Table 1. We combined the population prevalence, relative risk by smoker status, and proportion of smokers in the population to estimate age-and gender-specific prevalence by smoker status for each comorbidity, consistent with the approach taken in previous models [8,21]. The equation below shows how prevalence in the general population can be decomposed, where C is prevalence, P is the proportion within the population, RR is relative risk, general is general population, never is never smokers, former is former smokers and current is current smokers:…”
Section: State-transition Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The population prevalence of each comorbidity and relative risk for a smoker versus a former smoker were taken from various sourcesthe sources are shown in Table 1. We combined the population prevalence, relative risk by smoker status, and proportion of smokers in the population to estimate age-and gender-specific prevalence by smoker status for each comorbidity, consistent with the approach taken in previous models [8,21]. The equation below shows how prevalence in the general population can be decomposed, where C is prevalence, P is the proportion within the population, RR is relative risk, general is general population, never is never smokers, former is former smokers and current is current smokers:…”
Section: State-transition Modelmentioning
confidence: 99%
“…Research has shown that relative risks of developing comorbidities decreases with time since cessation, so the DES allows this [23]. The equation to model this has previously been used in smoking DES models [8] and considers age and gender in addition to time since cessation. Utilising baseline characteristics and history is a known advantage of DES models over state-transition models and this equation was not considered in the state-transition model (although it may be possible with multiple tunnel states).…”
Section: State-transition Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A patient who stops smoking for a full year is considered a smoking-cessation success. The model provides for the possibility of further attempts with the same drug, up to a maximum of 3, during a 5-year period starting from the first attempt to quit, both in case of failure after the initial attempt as well as in case of relapse after a successful attempt [34] . Relapse was estimated at 3% annually [35] .…”
Section: Model Structurementioning
confidence: 99%
“…One DES model (Xenakis et al 2011) measured smoking cessation abstinence and relapse one year after a treatment attempt using clinical trial data comparing varenicline to bupropion or placebo, but changes in lifetime smoking behavior and smoking-related illness were not evaluated. More recently, Getsios et al (2013) use DES to model individual quit attempts and lifetime risk of diseases is determined and quality of life and cost is assigned, rather than being modeled explicitly. We use DES to measure and compare the impact of different pharmacologic and non-pharmacologic smoking cessation interventions (NRT, Varenicline, bupropion, non-pharmacologic-assisted [i.e., cold turkey]) on lifetime smoking-related disease prevalence (chronic obstructive pulmonary disease [COPD], lung cancer, myocardial infarction [MI], stroke), mortality, quality of life, and costs at the US population level.…”
Section: Mayorga Reifsnider Wheeler and Kohlermentioning
confidence: 99%